(untitled) (Revista científica Olimpia, 2021)
The present investigative work is the result of an empirical investigation that solves the scientific problem: How to contribute to the care of the environment through recreational activities for children in the popular council "Castillo - Cen"? This research aims to: Develop recreational activities for the care of the environment of children in the popular council "Castillo - Cen". At work they are treated in an integrated manner, general criteria that are considered essential and representative for the preparation of recreational activities for the care of society’s environment. The results obtained are of great importance for the development of recreational - environmental actions of these children to form their behavior. "Protecting the environment is not a fashion, but a necessity"